Etheno-bridged azaacene spiro dimers [data] - Ahrens, Lukas; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Universität, 2023)
We present the synthesis of two sets of spiro-connected azaacene dimers. Their geometry and electronic coupling are critically determined by a secondary linker, i.e. an etheno- and an ethano-bridge.The core fragment of the etheno-bridged dimer corresponds to a conformationally locked cis-stilbene. Optoelectronic properties, single crystal X-ray structures and stability with respect to oxidation of the conjugated and non-conjugated dimers are reported and compared. The conjugated dimers exhibit smaller optical gaps and bathochromically shifted absorption maxima, but are prone to unexpected oxygen addition, dearomatizing one of the azaacene substituents. (2023-05-08)